2009
DOI: 10.1590/s0366-69132009000400013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of magnetic nanoparticles coated with silica through a sol-gel approach

Abstract: This paper investigates the influence of reaction medium pH on silica-coating of magnetite nanoparticles. Magnetite nanoparticles were prepared by means of a reduction-precipitation method using ferric chloride as a starting material, which was partially reduced to ferrous salts by Na2SO3 before alkalinizing with ammonia. The particles were coated by sol-gel method with either ammonia or HCl aqueous solutions for either base- or acid-catalyzed hydrolysis, respectively. Powder X-ray diffraction, Fourier-transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(74 citation statements)
references
References 33 publications
7
63
0
4
Order By: Relevance
“…In addition, it was found that the vibration band at 1,255 cm −1 is attributed to Fe‐O‐H bending modes in goethite . We are to state further that the peak at 1,023 cm −1 is represented as lepidocrocite . Going by the postulations in Tran et al, the characteristic band at 616 cm −1 could agree to the stretching and bending of Si–O bond for the silica .…”
Section: Resultsmentioning
confidence: 52%
“…In addition, it was found that the vibration band at 1,255 cm −1 is attributed to Fe‐O‐H bending modes in goethite . We are to state further that the peak at 1,023 cm −1 is represented as lepidocrocite . Going by the postulations in Tran et al, the characteristic band at 616 cm −1 could agree to the stretching and bending of Si–O bond for the silica .…”
Section: Resultsmentioning
confidence: 52%
“…Strong bands at \900 cm -1 in the nZVI alone (Fig. 4b), attributable in part to iron oxides on the surface Andrade et al 2009), are weaker in the composite, indicating less oxidation of agar supported Fe 0 . The agar support may have reduced Fe (oxy) hydroxide formation, similar to the effect of montmorillon-ite-supported nZVI (Yuan et al 2009).…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…1 and 2). The IR absorption bands in the 630-550 cm À1 range is attributed to the vibrations of Fe-O bonds in tetrahedral and octahedral sites 59 and must have been resulted from the split of the n 1 band at $570 cm À1 .…”
mentioning
confidence: 99%